Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $p=\sin 24^\circ$

  1. Then what would $\cos (24^\circ)$ be in terms of $p$?

  2. What would $\sin (168^\circ) \cdot \sin(-78^\circ)$ be in terms of $p$?

I'm not sure how to approach these as we have only started this section.


share|cite|improve this question
In the future, if you want to ask two questions, please ask them in separate posts. – MJD May 13 '13 at 14:44

You know that $\sin^2+\cos^2=1$. As $\sin(24)=p$ you have $p^2 + \cos^2(24)=1$. Solve this equation for $\cos(24)$. For the second part you can use some trigonometric theorems. For example $$ \sin(\alpha) \cdot \sin(\beta) = -\frac{1}{2} (\cos(\alpha+\beta) -\cos(\alpha - \beta))$$

This gives you $$\sin(168^\circ) \cdot \sin(-78^\circ)=-\frac{1}{2} ( \cos(90^\circ)- \cos(246^\circ))$$ We know that $\cos(90^\circ)=0$ and that $\cos(x+180^\circ)=-\cos(x)$ hence we have $$-\frac{1}{2} \cos(66^\circ)=-\frac{1}{2}\cos(90^\circ-24^\circ)=-\frac{1}{2} \sin(24^\circ)$$

share|cite|improve this answer

Part 1

Use the identity \begin{equation*} \sin^2A+\cos^2A=1\\ \cos^2 A={1-\sin^2 A} \end{equation*} so \begin{align*} \cos^2 24^\circ&={1-\sin^2( 24^\circ) }\\ \\ \\cos^2 24^\circ&={1-p^2 } \\ \\ \cos24^\circ&=\sqrt{1-p^2 } \end{align*} Here we only take positive value of square root because $24^\circ$ is in I quaderent and cos ratio in quaderent I is positive.

Part 2

\begin{align*} \sin 168^\circ \cdot \sin(-78^\circ) &=-\frac{2\sin 168^\circ\cdot\sin78^\circ}{2} \end{align*} Using the formula ${2\sin A\cdot\sin B}=\cos (A-B)-\cos(A+B)$ \begin{align*} \sin(168^\circ)\cdot \sin(-78^\circ)&=-\frac{\cos 90^\circ-\cos 246^\circ}{2} \\ &=\frac{\cos 246^\circ}{2}\\ &=\frac{\cos(270^\circ-24^\circ)}{2}\\ &=-\frac{\sin 24^\circ}{2}\\ &=-\frac{p}{2} \end{align*}

share|cite|improve this answer

enter image description here

My favorite method

$$\sin \theta = \cfrac{\text {opposite}}{\text{hypothenus}}=\cfrac p1,\quad \quad \cos\theta = \cfrac{\text {adjacent}}{\text{hypothenus}}$$ What is "adjacent"? By Pthagoras', we have $\quad \text{adjacent}^2+\text{opposite}^2=\text{hypothenus}^2$ so $$ \text{adjacent}^2 + p^2=1 \implies \text{adjacent}=\sqrt{1-p^2}$$ et voila! $$\cos\theta = \cfrac{\text {adjacent}}{\text{hypothenus}}=\cfrac{\sqrt{1-p^2}}{1}=\sqrt{1-p^2}$$

share|cite|improve this answer
Why did you write hypothenus and opposite in italics on the graphic and he variables in recto ? – Dominic Michaelis May 13 '13 at 15:54

Part 2

Method 1:

$\sin168^\circ=\sin(180^\circ-168^\circ)$ ( as $\sin(180^\circ-\theta)=\sin\theta$)

So, $\sin168^\circ=\sin12^\circ$

and $\sin(-78^\circ)=-\sin78^\circ$ as $\sin(-\theta)=-\sin\theta$

So, $\sin(-78^\circ)=-\sin(90^\circ-12^\circ)=-\cos12^\circ$

$$\implies \sin168^\circ\cdot\sin(-78^\circ)=\sin12^\circ\cdot(-\cos12^\circ)=-\frac{\sin (2\cdot12^\circ)}2=-\frac{\sin24^\circ}2$$

Method 2:

$\sin168^\circ=\sin(90^\circ+78^\circ)=\cos78^\circ$ as $\sin(90^\circ+\theta)=\cos\theta$

Again, $\cos78^\circ=\cos(-78^\circ)$ as $\cos(-\theta)=\cos\theta$

$$\implies \sin168^\circ\cdot\sin(-78^\circ)=\cos(-78^\circ)\cdot\sin(-78^\circ)=\frac{\sin 2(-78^\circ)}2$$ $$=\frac{\sin(24^\circ-180^\circ)}2=-\frac{\sin24^\circ}2$$ as $\sin(\theta-180^\circ)=-\sin(180^\circ-\theta)=-\sin\theta$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.